بر صغیر کے مشائخ شاذلیہ کی خدماتِ حدیث(ایک تاریخی جائزہ): Services for Hadith by Shazlia chain in Sub-continent (Historical Analysis) - Azhari, Dr Ali Akbar Al-azhar; Alam, Dr. Nadia (Al-Irfan, 2023)
It is a general misconception established by the people who are not on good terms with Tasawwuf that the Sufis are not well versed in Islamic sciences and proceed of their own free will without considering the Quran and Sunnah's teachings. And in this way, they had caused a situation of indifference to practical Islam, disbelief, and waywardness among the general Muslims. But, the ground reality is that the Sufis had been scholars of the first rank of Quran and Sunnah. And in almost all the chains of Tasawwuf they are found in abundance but in the Shazlia chain; an offshoot of Qadria, everyone was adept in Islamic sciences. The scholarly services of Jalal al-Din Sayuti(849-911) and Ibn e Hajar Haitami(909-974) in Arab countries and that of Muttaqi al-Hindi(802-1001) and Sheikh Abdul Haq(958-1056) based on research and preaching in the subcontinent cannot be ignored. The services put forth by the above-mentioned great men of letters are still unprecedented. This paper presents an analytical study of the services of the Shazlia chain particularly the teaching and propagation of Hadiths and in leveling the insurgencies of anti-Islamic forces like Mahdawiyyat.